2022
DOI: 10.1007/s40259-022-00543-9
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and Reactogenicity Profile of mRNA SARS-Cov-2 Vaccines from a Mass Vaccination Campaign in a Tertiary Hospital: Between-Vaccine and Between-Population Prospective Observational Study (VigilVacCOVID Study)

Abstract: Background The comparative safety profile of SARS-Cov2 vaccines requires further characterization in real-world settings. Objectives The aim of the VigilVacCOVID study was to assess the short-term safety of BNT162b2 and mRNA-1273 during the vaccination campaign of healthcare professionals (HCPs) and solid-organ transplant recipients (SOTRs) at a hospital clinic. Methods We conducted an observational, prospective, single-center, post-authoriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In further analysis of our data, we observed that local side effects were more common after MOD compared to BNT, however, only some systemic symptoms were significantly different between BNT and MOD. Previous studies reported a higher side effect rate after MOD compared to BNT [ 26 ]. Both vaccines are mRNA-based and are packed in lipid particles and contain no adjuvants.…”
Section: Discussionmentioning
confidence: 99%
“…In further analysis of our data, we observed that local side effects were more common after MOD compared to BNT, however, only some systemic symptoms were significantly different between BNT and MOD. Previous studies reported a higher side effect rate after MOD compared to BNT [ 26 ]. Both vaccines are mRNA-based and are packed in lipid particles and contain no adjuvants.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, when condition of patients with CKD is stable, COVID-19 vaccine is recommended. Studies have shown that the mRNA-1273 vaccine can induces higher antibody levels than the BNT162b2 vaccine, but the incidence of adverse events is also higher, requiring care in vaccine selection ( 84 , 85 ). Repeated doses of the COVID-19 vaccine improve the antibody levels and serum conversion rate of patients with kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…This was an observational, unicentric study with real-world data (RWD) that was implemented as a post hoc subanalysis of the VigilVacCOVID study [ 17 ]. The population of the VigilVacCOVID study included HCPs vaccinated with BNT162b2 and mRNA-1273 vaccines and SOTRs vaccinated with mRNA-1273.…”
Section: Methodsmentioning
confidence: 99%
“…Reactogenicity and tolerability results had been previously obtained during the vaccination campaign in the context of the VigilVacCOVID study. The characteristics of the implemented surveillance program, the methodology of the safety data collection, and the overall reactogenicity profile assessed in the main VigilVacCOVID study are described elsewhere [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation